The understanding of motor Takaful and insurance among staff in Universiti Teknologi Mara Puncak Alam / Nor Izzaty bt Isa - Isa, Nor Izzaty (Academy of Contemporary Islamic Studies (ACIS), 2018)
Takaful is an Islamic insurance concept and has been growing rapidly in Malaysia at the moment. Even though the majority of people in Malaysia are Muslim, they still don’t understand the real concept of takaful (Shamsuddin, Tang Howe Eng, & Lajim, 2016). Hence, the objectives of this study is to measure the understanding of motor takaful contract as well as to measure the understanding of motor insurance contract and to measure the comparison of the understanding between motor takaful and insurance contract among respondents. There are 20 respondents that involve in this study where all the respondents are staff at Universiti Teknologi Mara Puncak Alam. This study analyse by using Statistical Package for Social Sciences (SPSS). From the finding it can be said that the understanding of respondents towards takaful contract is in the moderate level but still they have the awareness and not involve in insurance as they may know that insurance contract has the prohibited elements where most of respondents choosing takaful for their motor policy. It can be seen that most of respondents still apply for takaful even though their understanding towards takaful contract is not fully understand. In general, the respondents understand insurance contract more than takaful contract but there is no much different between both.